Employee Performance at Agriculture and Fisheries Office, Sukoharjo Regency - Windaryanto, Bagas; Istiatin, Istiatin; Sudarwati, Sudarwati (Journal of Business Innovation and Research, 2023)
This study aims to determine the effect of simultaneously (simultaneously) or partially the variables of communication, competence, motivation and organizational culture on employee performance in the Department of Agriculture and Fisheries, Sukoharjo Regency. This research method uses a quantitative research design. The population of all employees working at the Department of Agriculture and Fisheries of Sukoharjo Regency is 200 employees. The sampling technique used in this study was a purposive sampling technique with a sample of 50 employees. Sampling is in accordance with research (Arikunto, 2019: 112), after calculating 25% of the population. Data collection using a questionnaire. Data analysis technique used statistical analysis, namely multiple linear regression test, F test, t test, and the coefficient of determination. The results of the study show that communication, competence, motivation and organizational culture partially and significantly influence the performance of employees in the Department of Agriculture and Fisheries of Sukoharjo Regency. Suggestions from this study, the Department of Agriculture and Fisheries of Sukoharjo Regency continues to improve existing communication, competence, motivation and organizational culture, so that it will make employee performance increase and become better than before.